Spanish Publishing Companies on Social Networks - Magadán Díaz, Marta; Rivas García, Jesús Israel (Publishing Research Quarterly, 2020)
The general goal of this research is to address the way in which the twenty-five first Spanish publishers in literature publication manage their social networks. For this, through the PRGS model, the weight of the main social networks (Facebook, Twitter and Instagram) in the digital marketing strategy of these Spanish publishing companies is analysed from a triple dimension: (a) the attraction of users, (b) content generation, and (c) users’ engagement to the brand. The study conducted on these twenty-five Spanish publishers concludes that Facebook is the one that generates the most fans, compared to Twitter and Instagram. Nonetheless, Twitter is the network most used to generate content. Finally, in terms of engagement, the results point out Instagram as the network where better results are obtained.
Keywords: electronic word-of-mouth; online reviews; brand community; Scopus; JCR